A Critical Analysis of the 2012 Centers for Medicare and Medicaid Services Provider Use and Payment Database. Issue 2 (February 2016) - Vyas, Krishna S.; Snapp, William K.; Rinker, Brian D.; Vasconez, Henry C.
Abstract : Background: On April 9, 2014, the Centers for Medicare and Medicaid Services released 10 million billing records of over 880, 000 physicians and other health care providers and accounts for over $1 billion in Medicare payments distributed in 2012. This action was part of an effort to improve the transparency, accountability, and affordability of the U.S. health care system. This study was performed to mine this unprecedented data set to delineate patterns of billing and reimbursement for plastic surgeons. Methods: The Centers for Medicare and Medicaid Services Provider Utilization and Payment Database was accessed to analyze 2012 plastic surgery claims data with respect to providers and beneficiaries, services, and reimbursements. Pivot tables and other methods were used by means of Microsoft Excel. Results: In 2012, a total of $133, 472, 772 was distributed to 3726 plastic surgery physician providers for 735 unique Healthcare Common Procedure Coding System codes for 1, 399, 404 procedure claims. Of specialty care, plastic surgery ranks twenty-sixth among 29 subspecialties for total Medicare payments. The average plastic surgeon was paid $35, 821.58 by the Centers for Medicare and Medicaid Services in 2012. Forty-six percent of plastic surgeons did not receive reimbursement for services from Medicare. Conclusions: The release of an enormous amount of provider level claims data by the Centers for Medicare and Medicaid Services may serve as a new tool for locating potential fraud, pinpointing needs, and assessing levels of growth in care. Plastic surgeons need to understand implications of changes to Medicare, which will likely affect patient mix, physician documentation, billing, coding, reimbursement, and active participation in quality reporting.